A New Class of Integrals Connected with Polynomials and Extended Generalized Mittag-Leffler Function - Nirmal Kumar Jangid; Sunil Joshi; Ekta Mittal (Sahand Communications in Mathematical Analysis)
The aim of the present investigation is to deal with integrals, which are connected with the extended generalized Mittag-Leffler function, Jacobi polynomial, and Bessel-Maitland function. Further, we are also considering the integral formulae, which involve various special functions. Interesting special cases of the main results are also considered. The results obtained here are general in nature and can presume numerous new integral formulae connecting the several types of polynomials.